SOME PROBLEMS OF JUDICIAL PRACTICE REGARDING WITNESS PARTICIPATION IN ADMINISTRATIVE-DELICIT PROCEEDINGS AND POSSIBILITIES OF THEIR SOLUTION - Rastorguev, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the study of some problems of judicial practice regarding the participation of a witness in administrative-delict proceedings and the possibilities of solving these problems in order to start a correct discussion. Research methods: the methodological basis of the study was made up of general scientific methods of cognition, with the help of which the author tried to find out the criteria for the procedure of bringing a witness to justice for contempt of court. Results: a number of significant features of the procedure of simultaneous continuation of the case within the framework of administrative-delict proceedings and bringing the witness in this case to administrative responsibility for contempt of court were revealed. Discussion: in this aspect, it is proposed to pay special attention to the need for the simultaneous implementation and adaptation to both of the specified procedures of both the trial of an administrative offense and the bringing of a witness to administrative liability for contempt of court of a number of innovations in the field of criminal proceedings in the part of the procedure for obtaining evidence and proving, which generally contains seven main stages. The approach of developing a single legal standard was supported, according to which the Law «On administrative procedure» should define standards for all types of administrative activity, including and the specified two procedures within the limits, so to speak, of double consideration of the administrative offense case. Attention was drawn to the need for unconditional implementation in the process of the specified fundamental reform of these two procedures from the point of view of reliable implementation of the rights of a witness with a dual procedural status as a witness and an offender in the system of basic European values.